谢裕民的本土书写 = On the local writings of Chia Joo Ming - 黄源乐 Ng, Violet (2016)
谢裕民在现代新华文学中是重要的作家之一，五十年代末出生于新加坡的谢裕民可说是随着国家的成长共同踏步，见证了这国家的发展与进步。本文将探讨谢裕民如何从本土的风貌、历史、意识及认同方面进行本土的书写，研究其作品中所抒发的本土情感。不只是极端的爱或恨，而是在对这城市的爱与恨之间寻找归属与认同，把日常生活的小细节融入到作品当中，使其更扣人心弦。他的作品从不同角度体现了新华文学追求自立化的过程，脱离中华文学母胎的怀抱并受到西方影响的同时展现属于自己新的的身份，将新加坡本土的风情、现象、及新加坡社会与政治的点点滴滴用简单易懂的文字传达，发挥一种属于新加坡的本土风采。Chia Joo Ming is one of the important writers in Singapore’s Contemporary Chinese Literary scene. Born in the late 1950s, Chia grew up together with the country, and witnessed the many changes and improvements that happened within. This thesis seeks to look into the local flavor of his works, how he presents that locality through his writing of the local sceneries, history, and identity. In them presents not the extreme ends of love or hate towards this city, but while seeking belonging and identity within this place, they write of an emotion intertwined between love and hate. Chia further intrigues his audiences by bringing the details of daily life into his works, creating sounds of resonance. Diving in through different angles and methods, he shows of Singapore Literature’s eagerness for independence, breaking away from the womb of China Literature which nurtured the first generations of works in Singapore and embracing also the influences coming from the West. Through simple words, he conveys life in Singapore, and through his depictions of the Singapore society, politics, and trends, Chia exudes the unique sides of this country.